Chinese guidelines related to novel coronavirus pneumonia - Tingting Qiu; Shuyao Liang; Monique Dabbous; Yitong Wang; Ru Han; Mondher Toumi (Taylor & Francis Group, 2020)
Background and Objective: China has managed to control the coronavirus disease (COVID-19) with confinement measurements and treatment strategies, while other countries are struggling to contain the spread. This study discusses the guidelines related to COVID-19 in China in order to provide important references for other countries in the fight against COVID-19. Methods: Chinese guidelines relevant to COVID-19 were systematically searched via the China National Knowledge Infrastructure database, YiMaiTong database, and World Health Organization (WHO) COVID-19 database on March 20th, 2020. Guideline information was extracted, including date of publication, source, objectives and the target population. Guidelines specific to the pharmacological treatment of COVID-19 were further investigated to identify the types of antivirus drugs recommended and to report on how treatment recommendations for COVID-19 have evolved overtime. Results: A total of 100 guidelines were identified, of which 74 were national guidelines and 26 were regional guidelines. The scope of included guidelines consisted of: the diagnosis and treatment of COVID-19, the management of hospital departments and specific diseases during the outbreak of COVID-19. Fifty-one of the included guidelines targeted overall COVID-19 patients, while the remaining guidelines concentrated on special patient populations (i.e. geriatric population, pediatric population, and pregnant population) or patients with coexisting diseases. Fifteen guidelines focused on the pharmacological treatments for all COVID-19 patients. Interferon, Lopinavir/Ritonavir, Ribavirin, Chloroquine, and Umifenovir represented the most recommended antivirus drugs. Among them, 7 Chinese guidelines have recommended Chloroquine Phosphate or Hydroxychloroquine for the treatment of COVID-19. Conclusions: China has generated a plethora of guidelines covering almost all aspects of COVID-19. Chloroquine, as one widely affordable treatment, was recommended by Chinese national guidelines and provincial guidelines. Considering the continuous debates around Chloroquine, confirmatory studies with robust methodology are awaited to address the unanswered questions on its potential benefits and risks on COVID-19.